2021
DOI: 10.2337/figshare.16847128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Foot Ulcer and Risk of Lower Limb Amputation or Death in People With Diabetes: A National Population-Based Retrospective Cohort Study

Abstract: Objective <p>To describe incidence of foot ulceration and amputation free survival associated with foot ulceration status in a national population-based cohort study of people with diabetes.</p> <p>Research Design and Methods</p> <p>The study population included 233,459 people with diabetes who were alive in Scotland on 1<sup>st</sup> January 2012 identified from the national population-based register (national prevalence 4.9%). Characteristics of patients identifie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This is the main difference to our study, in which we included only infected cases and also accepted DFI episodes without DFU. Nevertheless, all our findings and those of the literature suggest the same: a positive role of enhanced nutrition in DFU healing[8][9][10][11][12][13] and, consequently, cure of infection (with or without underlying ulcers).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…This is the main difference to our study, in which we included only infected cases and also accepted DFI episodes without DFU. Nevertheless, all our findings and those of the literature suggest the same: a positive role of enhanced nutrition in DFU healing[8][9][10][11][12][13] and, consequently, cure of infection (with or without underlying ulcers).…”
supporting
confidence: 77%
“…The multivariable Cox regression revealed that a low GNRI (hazard ratio (HR) 2.0, 95% confidence interval 1.4-3.0), a low PNI (HR 2.0, 95% CI 1.3-3.2), and a high CONUT score (HR 1.5, 95% CI 1.1-2.2) were all independently associated with high all-cause mortality [10]. In Scotland, Chamberlain et al [12] found a relation between a low BMI and the risk of amputation and/or all-cause mortality among diabetic patients. Most likely, the low BMI (<18.5 kg/m 2 ) reflected current malnutrition of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The list of uncertainties was at the planning stage aimed mainly for primary prevention of DFU but during the partnership process a few issues about treatment uncertainties remained highly important. In a nation‐wide study on people with type 1 and type 2 diabetes, 94.4% had no history of DFU at baseline, 6 justifying our focus on primary prevention, and not prevention of recurrence of DFU. The rankings of research uncertainties might have been different if this JLA priority setting partnership exclusively were about people with a history of DFU with, above all, increased risk of death 31 .…”
Section: Discussionmentioning
confidence: 99%